Interactions between buildings, building stakeholders and animals: A scoping review. (20th September 2022) - de Wilde, Pieter; Bleil de Souza, Clarice
Abstract: The preservation of biodiversity is a rising global concern and will have a major impact on the design and management of buildings and their immediate surroundings. Thus far, the majority of work on biodiversity and the built environment appears to focus on urban planning, project development, and the niche area of designing buildings with living walls and green roofs. Knowledge on the specific interaction between individual buildings and animals is fragmented, preventing holistic efforts to better manage these interactions. This paper presents the findings from a scoping study which captures the state-of-the-art about relationships between individual buildings, building stakeholders, and animals. It reviews the current body of knowledge and points out three areas of interest that are crucial for future work on this area of study: (1) different stakeholder perspectives of building stakeholders on animals in and around buildings (2) positive and negative interactions between individual buildings and their immediate surroundings with animals and (3) management of interactions between animals in and around buildings. Findings show that literature in relation to these three aspects is fragmented and contains multiple gaps in relation to which species need to be considered and how, including a total absence of mathematical models able to represent animal-building interactions. It calls for better engagement between built environment researchers and their counterparts in biological sciences to collect appropriate data and extract relevant information from it, enhancing knowledge on complex biological processes towards producing shared understanding and developing integrated actions. Highlights: Only fragmented knowledge on interaction between specific buildings and animals. Widely different stakholder perspectives on animals in and around buildings. Positive and negative interactions between buildings and animals. Animal management around buildings seems biased towards pest management.